2022
DOI: 10.3390/biology11111666
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Date Palm Genotypes on Rhizobacterial Community Structures under Saline Environments

Abstract: Some genotypes of date palms (Phoenix dactylifera L.) are salt-tolerant; however, salinity significantly affects others. This study aimed to determine the root epiphytic bacterial contributions to the salt tolerance mechanism in the date palm and to verify if the salt-tolerant “Umsila” and the salt-susceptible “Zabad” cultivars have different bacterial communities. Therefore, the epiphytic bacterial community structures were investigated in both cultivars when grown under control and salinity conditions. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Advanced DNA sequencing technologies, such as NGS, have the potential to enhance the efficient identification and subsequent successful isolation of microbial organisms [ 29 ]. Comparative microbiome analysis is a versatile means of identifying microbes that grow under conditions of high salinity in the rhizosphere of a specific plant genotype [ 22 ]. Therefore, this study employed NGS technology to study the mycobiomes of two distinct genotypes of date palms, each with different salinity tolerance capacities, to characterize mycobiomes in date palms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Advanced DNA sequencing technologies, such as NGS, have the potential to enhance the efficient identification and subsequent successful isolation of microbial organisms [ 29 ]. Comparative microbiome analysis is a versatile means of identifying microbes that grow under conditions of high salinity in the rhizosphere of a specific plant genotype [ 22 ]. Therefore, this study employed NGS technology to study the mycobiomes of two distinct genotypes of date palms, each with different salinity tolerance capacities, to characterize mycobiomes in date palms.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the rhizobacterial communities of the same date palm cultivars (‘Umsila’ and ‘Zabad’) found that the plant genotype did not significantly impact the epiphyte bacterial community structure under salinity stress [ 22 ]. In contrast, the results reported here reveal that the fungal communities are affected by salinity in the mycobiomes of both date palm genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations